Effectiveness and safety of oral anticoagulants for non-valvular atrial fibrillation: a population-based cohort study in primary healthcare in Catalonia - Giner-Soriano, Maria; Ouchi, Dan; Vives, Roser; Vilaplana-Carnerero, Carles; Molina, Andrea; Vallano, Antoni; Morros, Rosa (Frontiers in Pharmacology, 2023)
Objectives Our objective was to analyse effectiveness and safety of oral anticoagulants (OAC) for stroke prevention in non-valvular atrial fibrillation. Material and methods Population-based cohort study including adults initiating OAC, either direct oral anticoagulants (DOAC) or vitamin K antagonists (VKA), during 2011-2020. Data source: SIDIAP, capturing information from the electronic health records of Primary Health Care in Catalonia, Spain. Study outcomes: stroke, cerebral and gastrointestinal (GI) haemorrhage, assessed by patients’ subgroups according to different clinical characteristics. Results We included 90,773 patients. Male sex, older than 75, previous event, peripheral artery disease, deep vein thrombosis, or receiving antiplatelets, antidiabetics or proton pump inhibitors (PPI) was associated with higher stroke risk. For DOAC-treated, treatment switch increased stroke risk, while being adherent had a protective effect. Men, antidiabetic treatment or a previous event increased the risk of cerebral bleeding. Receiving DOAC had a protective effect in comparison to VKA. For DOAC-treated, treatment switch increased, and adherence decreased the bleeding risk. Men, people with chronic kidney disease or a previous event posed an increased risk of GI bleeding, whereas receiving PPI had a protective effect. For DOAC-treated, switch was associated with a higher bleeding risk. Conclusions Being men, a previous event and DOAC-switch posed a higher risk for all study outcomes. DOAC had a protective effect against cerebral bleeding in comparison to VKA. Adherence to DOAC resulted in lower risk of stroke and cerebral bleeding. We found no differences in the risk of stroke and GI bleeding when we compared DOAC vs. VKA.